An integrated full-head OPM-MEG system based on 128 zero-field sensors - Alem, Orang; Hughes, K. Jeramy; Buard, Isabelle; Cheung, Teresa P.; Maydew, Tyler; Griesshammer, Andreas; Holloway, Kendall; Park, Aaron; Lechuga, Vanessa; Coolidge, Collin; Gerginov, Marja; Quigg, Erik; et al. (Frontiers in Neuroscience, 2023)
Compact optically-pumped magnetometers (OPMs) are now commercially available with noise floors reaching 10 fT/Hz1/2. However, to be used effectively for magnetoencephalography (MEG), dense arrays of these sensors are required to operate as an integrated turn-key system. In this study, we present the HEDscan, a 128-sensor OPM MEG system by FieldLine Medical, and evaluate its sensor performance with regard to bandwidth, linearity, and crosstalk. We report results from cross-validation studies with conventional cryogenic MEG, the Magnes 3,600 WH Biomagnetometer by 4-D Neuroimaging. Our results show high signal amplitudes captured by the OPM-MEG system during a standard auditory paradigm, where short tones at 1000 Hz were presented to the left ear of six healthy adult volunteers. We validate these findings through an event-related beamformer analysis, which is in line with existing literature results.